The effect of the antisickling compound GBT1118 on the permeability of red blood cells from patients with sickle cell anemia. Issue 6 (27th March 2019) - Al Balushi, Halima; Dufu, Kobina; Rees, David C.; Brewin, John N.; Hannemann, Anke; Oksenberg, Donna; Lu, David C.‐Y.; Gibson, John S.
Abstract: Sickle cell anemia (SCA) is one of the commonest severe inherited disorders. Nevertheless, effective treatments remain inadequate and novel ones are avidly sought. A promising advance has been the design of novel compounds which react with hemoglobin S (HbS) to increase oxygen (O2 ) affinity and reduce sickling. One of these, voxelotor (GBT440), is currently in advanced clinical trials. A structural analogue, GBT1118, was investigated in the current work. As RBC dehydration is important in pathogenesis of SCA, the effect of GBT1118 on RBC cation permeability was also studied. Activities of Psickle, the Gardos channel and the KCl cotransporter (KCC) were all reduced. Gardos channel and KCC activities were also inhibited in RBCs treated with Ca 2+ ionophore or the thiol reagent N ‐ethylmaleimide, indicative of direct effects on these two transport systems. Consistent with its action on RBC membrane transporters, GBT1118 significantly increased RBC hydration. RBC hemolysis was reduced in a nonelectrolyte lysis assay. Further to its direct effects on O2 affinity, GBT1118 was therefore found to reduce RBC shrinkage and fragility. Findings reveal important effects of GBT1118 on protecting sickle cells and suggest that this is approach may represent a useful therapy for amelioration of the clinical complications of SCA. Abstract : Aromatic aldehydes including GBT compounds have been designed to increase oxygen affinity of HbS and act as antisickling agents to reduce clinical signs. Here we look at their effects on red cell membrane cation permeability and red cell volume. We show that in addition to increasing oxygen affinity these compounds also inhibit cation loss and maintain red cell hydration. Consequent reduction in concentration of HbS may act synergistically to reduce pathology.